2020
DOI: 10.31234/osf.io/2vt4k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Replications, Comparisons, Sampling and the Problem of Representativeness in Animal Cognition Research

Abstract: Research in animal behaviour often involves small and idiosyncratic samples. This can constrain the generalizability and replicability of study’s results and prevent meaningful comparisons between samples. However, there is little consensus about what constitutes a replication and what makes a strong comparison in animal research. We apply a resampling definition of replication to answer these questions in Part 1 of this article, and in Part 2, we focus on the problem of representativeness in animal research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…Despite the scarcity of evidence regarding the reliability of comparative psychology findings, researchers in ecology and evolution (fields closely related to ours) report engaging in QRPs at comparable levels to other areas of psychology, with 51% of respondents reporting engaging in HARKing, 42% collecting additional data after conducting statistical analyses to check for significance, and 64% selectively reporting 'positive' results and not including non-significant findings (Fraser et al, 2018). On a more positive note, a recent survey of 63 papers in the animal physical cognition literature showed that some papers (10-17%) did report negative findings, and a further 24-46% made inconclusive claims, demonstrating that 'negative' findings can and have been published (Farrar et al, 2021).…”
Section: How Reliable Are Findings In Comparative Psychology?mentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the scarcity of evidence regarding the reliability of comparative psychology findings, researchers in ecology and evolution (fields closely related to ours) report engaging in QRPs at comparable levels to other areas of psychology, with 51% of respondents reporting engaging in HARKing, 42% collecting additional data after conducting statistical analyses to check for significance, and 64% selectively reporting 'positive' results and not including non-significant findings (Fraser et al, 2018). On a more positive note, a recent survey of 63 papers in the animal physical cognition literature showed that some papers (10-17%) did report negative findings, and a further 24-46% made inconclusive claims, demonstrating that 'negative' findings can and have been published (Farrar et al, 2021).…”
Section: How Reliable Are Findings In Comparative Psychology?mentioning
confidence: 99%
“…Even within a single strain of mice housed in tightly controlled, highly standardized lab environments, there is evidence that systematic differences in stress-like behaviours can occur across labs (Crabbe et al, 1999). A re-analysis of data from Mac-Lean et al ( 2014)-a mutli-site, multi-species comparison of performance in two inhibitory control tasksrevealed some instances of large within-species variation in performance between testing sites (Farrar et al, 2021). Squirrel monkeys' performance on the cylinder task was 60% correct in Edinburgh, compared with only 5% correct in Kyoto.…”
Section: Comparing Across Testing Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychological science has been riddled with problems of non-replicable results (Collaboration, 2015). Animal cognition research shows many of the characteristics that have been identified to yield a low replication rate in other psychological fields (Farrar et al, 2020b;Stevens, 2017). Furthermore, replication attempts are rare in animal cognition research (Farrar et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%